Comparative de novo Transcriptome Analysis of Two Cultivars With Contrasting Content of Oil and Fatty Acids During Kernel Development in Torreya grandis - Zhang, Chi; Liu, Haokai; Zhang, Hui; Dang, Wanyu; Zhou, Caihong; Zhang, Min (Frontiers in Plant Science, 2022)
Vegetable oil is an indispensable nutritional resource for human health and mainly characterized by the composition and content of fatty acids (FAs). As a commercial species of gymnosperm, Torreya grandis produces oil-rich nuts with high unsaturated fatty acids content in the mature kernels. In this study, two cultivars, T. grandis ‘Xifei’ and T. grandis ‘Dielsii,’ with distinct oil content were employed to compare the profiles of FAs accumulation during kernel development. The accumulation rate of oil content was significantly different between ‘Xifei’ and ‘Dielsii.’ Besides, the final oil content of ‘Xifei’ (52.87%) was significantly higher than that of ‘Dielsii’ (41.62%) at maturity. The significant differences in main FAs were observed at almost each kernel development stages between the two cultivars. C16:0, C18:1, and C20:3 FA exhibited different accumulation patterns between cultivars. The content and the initiation of accumulation of C20:3 FA were different between the two cultivars. To explore the molecular mechanism associated with different content of oil and FAs between two cultivars, de novo transcriptome of kernels was compared between ‘Xifei’ (high oil) and ‘Dielsii’ (low oil) at three stages of oil accumulation, respectively. Totally 142,213 unigenes were assembled and 16,379 unigenes with a length of over 1,000 nt were successfully annotated, including 139 unigenes related to FA biosynthesis, elongation, and metabolism. Compared with ‘Dielsii,’ totally 1,476, 2,140, and 1,145 differentially expressed genes (DEGs) were upregulated in ‘Xifei’ at the stage of the initiative, the rapid rise, and the stationary oil accumulation, respectively; the number of downregulated DEGs reached 913, 1,245, and 904, respectively. Relative expressions of 11 DEGs involved in FAs biosynthesis and metabolism were confirmed by RT-qPCR. Abundant differentially expressed transcription factors and pathway DEGs were correlated to oil and FAs according to Pearson’s correlation analysis between transcriptome and metabolites (oil and FAs), suggesting their contributions to the differential oil and FAs between the two cultivars during kernel development of T. grandis. To conclude, our findings can provide novel insights into the developmental differences in metabolites and de novo transcriptome correlated to lipid accumulation and FA synthesis of kernels between cultivars with contrasting oil deposits and demystify the regulatory mechanism of high oil accumulation in T. grandis.